Desvelando sentidos, descortinando práticas: representações sociais docentes sobre o ensino com pesquisa na formação inicial de professores de uma universidade pública baiana - Almeida, Rosângela Maria Barrêto dos Santos de (2018)
This dissertation presents the results of an investigation developed in the Graduate Program in Education of the State University of Feira de Santana-BA, whose objective was to understand, through social representations, how teaching with research is treated in the pedagogical practice of teachers of undergraduate courses at a public university in Bahia. In this sense, we use as theoretical-methodological reference the Theory of Social Representations of Moscovici (1978, 2005) in the approaches of Abric (1994) and Jodelet (1993). During the study we discussed the following concepts: Teaching and Learning Strategies in Teaching Practice (Freire (2001, 1997), Backer (2012), Demo (1997, 2001,2003, 2004, 2011), Anastasiou and Alves (2005), and Chernobyl (2002), Anastasiou and Alves (2005), Freire (1980, 1987), Severino (2008), Nova and Soares (2012), and Research in Pedagogical Practice (1996), Cunha (1996) and Gatti (2014)) and Initial Formation in the Present Context (Ibernón (2009), Tardif (2002), Garcia (1999), Ribeiro (2015), Pereira. This is a quantitative, descriptive and exploratory study that used as a methodological strategy the application of the Free Word Association Technique (TALP) with 50 teachers from undergraduate courses in the area of humanities, semi-structured interviews with 05 professors of the course of Degree in Geography and the Hierarchical Successive Triage for more or understanding of the meanings attributed by the subjects to teaching with research and to the research practices offered by the teachers during the training. The research revealed, among other aspects that, although teachers consider the research important for the construction of knowledge, the teachers' representations bring evidence that research as a teaching-learning strategy still needs to be consolidated in the pedagogical dimension of the teacher educators, confirming that in practice, research still appears as one related to the scientistic character of the university, in what concerns the production of knowledge, evidencing as a difficult element the reading and the student profile, and as a driving force for the practice of research, the breaking of the traditional paradigm and the need for continuing teacher training. The results seem to have as a background, the traditional teaching-learning conception, whose transmissive practices are still present.